Initiation of Disaster Resilient Villages in Tubo Village, North Ternate District - Ternate City - Abdul Kadir Dahlan Arif; Muhammad Djunaidi; Ida Kurnia Waliyanti (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The city of Ternate is a small city on a quaternary volcanic island with a strato volcano type that develops in the Halmahera island area as part of the Pacific circumference. The city of Ternate, as a small city that continues to develop, has complex problems related to limited building space and the potential threat of very diverse natural disasters. Tubo Village is one of the areas that is a potential threat point from the Gamalama volcanic eruption. The Tubo sub-district area is part of the succession of mature to old Gamalama volcanoes which have episodes of Gamalama volcanic eruptions, including direct eruption impacts in the form of laharic material, volcanic ash and lava flows. Tubo Village also has a history of the impact of volcanic eruptions in the form of laharic floods which have had an impact on physical victims and fatalities. Disaster Resilient Village is one of the best solutions that must be implemented with the aim of building the preparedness of Tubo residents to face volcanic eruption disasters. This initiation program is a collaboration with Pertamina FT Babullah and the Ternate City Government.